The influence of teaching variables in the educational processes of students with rare diseases - García-Perales, Ramón; Palomares-Ruiz, Ascensión; García-Toledano, Eduardo; Martín-García, María Inés (Frontiers in Psychology, 2023)
Teachers have a key role in their students’ educational inclusion processes. Numerous variables influence their professional work that determine how they approach teaching their students. In this study, 574 teachers teaching non-university educational stages in the Autonomous Community of Castilla-La Mancha were queried about their knowledge and perceptions regarding students with rare diseases, examining the extent to which there were personal variables that could have an impact on that. The results indicate the need to expand training to increase levels of knowledge about rare diseases in the educational field. All of the evaluated teaching variables were statistically significant: sex, age, job position, teaching experience, and higher qualifications. This shows that there are teaching variables that influence the inclusion of students with rare diseases. Being aware of them should be a priority in order to increase teacher empowerment for the delivery of inclusive educational processes. All students exhibit distinctive characteristics and teachers play an essential role in offering them an individualized, quality educational response.